2021
DOI: 10.1002/sdtp.14468
|View full text |Cite
|
Sign up to set email alerts
|

45.1: High‐Performance Deep Blue OLEDs with EQE up to 31%

Abstract: The low efficiency of blue devices has been a bottleneck problem for OLED panel manufacturers for a long time. In recent years, TASF‐OLED has attracted great attention because of the high external quantum efficiency and color purity, which makes it a promising technology for high efficiency deep blue OLEDs. In this paper, we present our latest development of TADF material for deep blue TASF‐OLEDs with an emission peak at 460 nm and a high external quantum efficiency up to 31 %.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Furthermore, TASF OLED use a narrow-emissive fluorescent molecule as the guest emitter, producing improved emission color purity. We reported a blue TASF OLED with external quantum efficiency as high as 31% with emission peak in the 460 nm region [1] .…”
Section: Introductionmentioning
confidence: 98%
“…Furthermore, TASF OLED use a narrow-emissive fluorescent molecule as the guest emitter, producing improved emission color purity. We reported a blue TASF OLED with external quantum efficiency as high as 31% with emission peak in the 460 nm region [1] .…”
Section: Introductionmentioning
confidence: 98%
“…Furthermore, TASF OLED uses a narrow‐emissive fluorescent molecule as the guest emitter, producing improved emission color purity. We reported a blue TASF OLED with external quantum efficiency as high as 31% with emission peak in the 460 nm region 9 …”
Section: Introductionmentioning
confidence: 99%
“…We reported a blue TASF OLED with external quantum efficiency as high as 31% with emission peak in the 460 nm region. 9 Nevertheless, it remains a major challenge to achieve sufficient operation lifetime in such a highly efficient TASF OLED to meet the display requirements. We have systematically explored various strategies toward stable deep blue TASF OLEDs and found that pumping triplet excitons on TADF sensitizer all the way to fluorescent dopant in a fast and efficient manner is critical to stabilize the devices.…”
Section: Introductionmentioning
confidence: 99%